EFEKTIVITAS SISTEM PELAYANAN RAKYAT SIDOARJO (SIPRAJA) SEBAGAI PELAYANAN PUBLIK DI DESA GEMPOLSARI KABUPATEN SIDOARJO - Angela Christiana Yosephine; Tukiman (Halu Oleo University, 2024)
The Sidoarjo Regency Government presents innovative public service products based on electronic technology in the form of applications, namely the Sidoarjo People's Service System (SIPRAJA). This research aims to measure the effectiveness of SIPRAJA as a public service in Gempolsari Village, Sidoarjo Regency. The quantitative research method used is one variable in a descriptive approach based on the theory of innovation characteristics according to Rogers which requires a sample of 100 respondents. This research has the results that the indicators of relative superiority, compatibility, complexity, testability and observability are very effective. So, the overall conclusion is that the effectiveness of SIPRAJA in Gempolsari Village, Sidoarjo Regency with a final result of a percentage value of 69% is included in the very effective category.